Introduksi Pemijahan Buatan Dan Probiotik Dalam Meningkatkan Produksi Benih Lele Di Junrejo Malang - Wahyu Endra Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
This community service was conducted to asssist catfish farmers to solve their problem in producing catfish fry. Several problems identified in the initial survey were low quality of catfish fry as some broodstock were too old, high cost of feed, lack of capital and lack of production and financial management. Some activities undertaken in this community service were: introduction of broodstock, concrete ponds, workshop on induced spawning and probiotic production, training of production and financial management, demo-pond and monitoring and evaluation. The results of demo-ponds showed that introduction of broodstock, concreate ponds, induced spawning method, application of probiotics increased the catfish fry production up to 59,1 % which then improved the farmers income up to 49,4%.